2020
DOI: 10.1074/jbc.ra120.013801
|View full text |Cite
|
Sign up to set email alerts
|

FUS contributes to mTOR-dependent inhibition of translation

Abstract: The amyotrophic lateral sclerosis (ALS) and frontotemporal degeneration (FTD)-linked RNA-binding protein called fused in sarcoma (FUS) has been implicated in several aspects of RNA regulation, including mRNA translation. The mechanism by which FUS affects the translation of polyribosomes has not been established. Here we show that FUS can associate with stalled polyribosomes and that this association is sensitive to mTOR (mammalian Target of Rapamycin) kinase activity. Specifically, we show that FUS associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 85 publications
5
32
1
Order By: Relevance
“…Our data also confirms previous data showing that mutations in FUS affect protein synthesis 36 , 43 . Moreover, translation defects appear to be specific to the degree of mislocalised cytoplasmic FUS depending on the mutation present.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data also confirms previous data showing that mutations in FUS affect protein synthesis 36 , 43 . Moreover, translation defects appear to be specific to the degree of mislocalised cytoplasmic FUS depending on the mutation present.…”
Section: Discussionsupporting
confidence: 93%
“…As with our previous data, FUS R514G led to an increase in translation in affected soma and neurites whereas FUS ΔNLS led to a decrease. Previous reports have demonstrated that mutant FUS interacts with polyribosomes and that a toxic ‘gain of function’ in the cytoplasm affects translation 43 . Therefore, it is likely that the changes in global translation alongside the mitochondrial abnormalities we observe lead to the synaptic abnormalities exhibited by each specific mutant.…”
Section: Discussionmentioning
confidence: 99%
“…We report that expression of FUS mutants at endogenous levels impairs translation, both in physiological models of disease (heterozygous FUS mutant mice) and in MNs carrying homozygous mutations. A recent study, where FUS was overexpressed in human embryonic kidney (HEK) 293 cells, has shown that FUS-mediated translation inhibition was associated with increased cosedimentation of FUS mutants with polysomes ( 38 ). In our model, however, we find that endogenously expressed mutant FUS does not associate with the translational machinery using biochemical and imaging approaches, a difference that could be due to the overexpression of the protein or to an alternative regulation in HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…FUS function is closely linked to regulation of mRNA translation (Baron et al , 2013; Baron et al ., 2019; Kamelgarn et al ., 2018; Sévigny et al , 2020; Yasuda et al , 2013). In line with this, we saw that expression of FUS PM enhanced protein translation compared to FUS WT (Figure 5D).…”
Section: Discussionmentioning
confidence: 99%